ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI PADA SUB BIDANG PERBENDAHARAAN BAGIAN KEUANGAN SEKRETARIAT DAERAH KABUPATEN KUTAI KARTANEGARA - Hubaib, Futum (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The purpose of this study is to know and examine matters as follows: Factors that affect the employee job satisfaction in Sub Division Treasury Finance Division Regional Secretariat Kutai Kartanegara and know the most dominant factors affect employee job satisfactionTo analyze the data obtained by researchers using multiple regression analysis tools and SPSS application (Statistic Product and Service Solution) Based on the results of data analysis using SPSS and discussion then the conclusions can be put forward are:The resulting regression equation is Y = 2.779 + 0.030X1 + 0.136 X2. The resulting value is marked positive which means having a direct relationship. The constant value (a) of 2.779 states that if X1 and X2 are equal to zero. Then the satisfaction of cooperation with 2.779 or can be said if there is no variable of employee factor (X1) and job factor (X2) then job satisfaction (Y) equal to 2,779.Result of F test calculation, Fcount value is 4,303 with significance level 0,000. Since probability (0,000) is less than 0.05, regression model can be used to predict job satisfaction, or it can be said that the variable of employee factor and work factor that applied together have an effect on job satisfaction.The value of R Square (Determination R or R2) shows the number of 0.806 from 8982, thus it can be said that the independent variables of employee and occupational factors have an influence of 0.806 or 8.06% have the level of variable relations factor employee and job factors against job satisfaction is very strong. Based on the above description, the first hypothesis has been presented.Result of t test calculation between employee with job satisfaction, it can be seen that thitung> ttable or 2,815> 2,021 with significance level 0,000 <0,005, indicate that tcount> ttable or 2,743> 2,021 with significance level 0,001 <0,005 meaning work variable variable partially significantly indicating its effect on job satisfaction. So variable of employee factor have the most dominant influence influence job satisfaction compare of work factor variable. Thus the second hypothesis that the researcher submitted was accepted.